"HAVAS QILGAN JONKUYAR USTOZIM ODILJON NAZAROV" (E Conference Zone, 2022)
This article reflects the diligence, kindness of our teacher, Professor Odiljon Nazarov, and his upbringing of students in the spirit of devotion to the Motherland.